Penyuluhan Tentang Bahaya Abortus Di SMA Negeri 1 Kairatu - Netty Taribuka; Wa Ode Ningko (Jurnal Pengabmas Masyarakat Sehat, 2021)
Education on sexual and reproductive health for adolescents in Indonesia has not been fully accepted by the community. This is influenced by the complex environment of social, cultural and religious life. Many people consider that sexual and reproductive health education is a taboo subject to discuss among adolescents. These conditions make adolescents confused in determining their reproductive health behavior. However, over time, the influence of Western culture has brought freedom and open access to information so as to provide opportunities for adolescents to have negative behaviors in reproductive health. The prevalence of sexually active behavior in male adolescents (56.6%) is higher when compared to adolescent girls (43.7%). The problem of abortion in adolescents needs to be seriously addressed, because this problem occurs mostly in developing countries such as Indonesia due to the lack of access to information about abortion. This is evident from many studies which state that the high number of unsafe abortions that causes death is due to the lack of knowledge of young women about the dangers of abortion.Keywords: danger of abortion